Central sensitization, illness perception and obesity should be considered when interpreting disease activity in axial spondyloarthritis. (25th January 2021) - Kieskamp, Stan C; Paap, Davy; Carbo, Marlies J G; Wink, Freke; Bos, Reinhard; Bootsma, Hendrika; Arends, Suzanne; Spoorenberg, Anneke
Abstract: Objectives: Many patients with axial spondyloarthritis (axSpA) report persistent pain even when treated with anti-inflammatory agents. Our aim was to explore the presence of central sensitization (CS) and different types of illness perceptions in patients with axSpA, and to assess their associations with disease activity assessments. Methods: Consecutive outpatients from the Groningen Leeuwarden Axial Spondyloarthritis (GLAS) cohort were included. Besides standardized assessments, patients filled out the Central Sensitization Inventory (CSI), Illness Perception Questionnaire (IPQ-R) and Pain Catastrophizing Scale (PCS). Univariable and multivariable linear regression analyses were used to investigate the association between questionnaire scores, patient characteristics and disease activity assessments ASDASCRP, BASDAI and CRP. Results: We included 182 patients with a mean symptom duration of 21.6 years. Mean ASDASCRP was 2.1, mean BASDAI 3.9, and median CRP 2.9. Mean CSI score was 37.8 (scale 0–100) and 45% of patients scored ≥40, indicating a high probability of CS. CSI score, IPQ-R domain identity (number of symptoms the patient attributes to their illness), and IPQ-R domain treatment control (perceived treatment efficacy), and obesity were significantly and independently associated with both ASDASCRP and BASDAI, explaining a substantial proportion of variation in these disease activity scores ( R 2 =0.35 and R 2 =0.47, respectively). Only obesity was also independently associated with CRP. Conclusion: CS may be common in patients with long-term axSpA. CS, as well as specific illness perceptions and obesity were all independently associated with the widely used (partially) patient-reported disease activity assessments ASDASCRP and BASDAI. Treating physicians should take this into account in the follow-up and treatment of their patients.